(untitled) (Research, Society and Development, 2021)
The study addresses the transfer of patients between sectors and at hospital discharge, aiming to identify protocols and instruments used at the time of transition, which ensure the continuity of patient care. Objective: To analyze the transfer tools used by nurses that contribute to the continuity of care. Methodology: The review followed six steps: definition of the research question, delimitation of inclusion and exclusion criteria/sampling or data search, data collection, data analysis/analysis of findings, interpretation of results and summary of the review. The search was performed in the following databases: Virtual Health Library, Academic Search Premier and PubMed. The same search strategy was applied to all of them and two filters: full texts and published from 2016 to 2021. Results: The search identified 479 articles, which were analyzed using the PRISMA flowchart. The 8 selected articles highlighted the role of nurses as planners for the patient’s discharge and/or transfer, in addition to the fact that the most common tools that provide security and strengthen the communication process between professionals are based on forms and verbal communication. Final considerations: It was identified that the most used tools and strategies are verbal transmission, checklists and forms, in addition to some computerized systems that are being developed and are gaining more relevance today. Nursing played a leading role in the theme, which strengthens professional identity and visibility.